2002
DOI: 10.1103/physrevb.66.094410
|View full text |Cite
|
Sign up to set email alerts
|

Structural, magnetic, and electrical properties of single-crystallineLa1xSrx

Abstract: We report on structural, magnetic and electrical properties of Sr-doped LaMnO3 single crystals for doping levels 0.4 ≤ x ≤ 0.85. The complex structural and magnetic phase diagram can only be explained assuming significant contributions from the orbital degrees of freedom. Close to x = 0.6 a ferromagnetic metal is followed by an antiferromagnetic metallic phase below 200 K. This antiferromagnetic metallic phase exists in a monoclinic crystallographic structure. Following theoretical predictions this metallic an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
168
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(191 citation statements)
references
References 41 publications
(74 reference statements)
17
168
0
6
Order By: Relevance
“…This is also a superparamagnetic characteristic. 20 Unlike single crystal and bulk samples of LSMO, [24][25][26] Figure 1(c) shows the magnetization of the sample at different temperatures. It should be noted that it is far from saturated even in 5 T and varies almost linearly with magnetic field for l 0 H > 1 T, suggesting that the ferromagnetism is due to spin canting in an underlying antiferromagnetic structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also a superparamagnetic characteristic. 20 Unlike single crystal and bulk samples of LSMO, [24][25][26] Figure 1(c) shows the magnetization of the sample at different temperatures. It should be noted that it is far from saturated even in 5 T and varies almost linearly with magnetic field for l 0 H > 1 T, suggesting that the ferromagnetism is due to spin canting in an underlying antiferromagnetic structure.…”
Section: Resultsmentioning
confidence: 99%
“…0.5, the DE interaction mediates ferromagnetic coupling between Mn 3þ and Mn 4þ ions within the ab plane and the SE interaction produces out of plane antiferromagnetic coupling along the c axis, resulting in the A-type antiferromagnetic ground state. 24,25 A canted ferromagnetic structure with a net moment 1 l B /Mn has slightly higher energy, but it can be stabilized by entropy if the canting is random. However, the antiferromagnetic state becomes increasingly unstable in small particles compared to the canted state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that the total 42 magnetic moment [16,17], the coercive field [18], the magnetic 43 anisotropy [19,20], and the Curie temperature [17,21] [25]. The magnetic state of 72 LSMO is reflected in its transport properties.…”
mentioning
confidence: 99%
“…Strong ME coupling alternatively can occur at the interface of certain materials, [13][14][15] one of which is the interface between La 0.7 Sr 0.3 MnO 3 (LSMO) and PbZr 0.2 Ti 0.8 O 3 (PZT). La 1Àx Sr x MnO 3 exhibits a rich phase diagram 16,17 at varying doping level x. PZT is a strong room temperature ferroelectric (FE) material. In recent work on ME interfaces, a large magnetization modulation was found by Lu et al 18 19 In addition to these observations, Mn valence is also known to associate with the LSMO magnetization.…”
mentioning
confidence: 99%